A ZnO/ZnFe2O4 n–n heterojunction and Au loading synergistically improve the sensing performance of acetone - Qin, Qixuan; Li, Asu; Fan, Yizhuo; Zhang, Xindong (Inorganic chemistry frontiers, 2022)
In this work, Au nanoparticle-loaded ZnO/ZnFe2O4 (Au-ZnO/ZnFe2O4) microspheres were prepared using a combination of a two-step hydrothermal process and a co-precipitation method. The SEM and TEM analyses showed that the synthesized Au-ZnO/ZnFe2O4 samples were microspheres with a yolk–shell structure assembled from nanosheets. Gas-sensitive performance tests indicated that Au-ZnO/ZnFe2O4 showed the highest response to 100 ppm acetone (18.18), higher than those of ZnFe2O4 (8.4) and ZnO/ZnFe2O4 (11.6). In addition, the optimum operating temperature of Au-ZnO/ZnFe2O4 decreased from 279 to 206 °C compared to ZnFe2O4 and ZnO/ZnFe2O4. In addition, Au-ZnO/ZnFe2O4 yolk–shell microspheres exhibited fast response and recovery times (4 and 23 s, respectively). The sensor has a lower limit of acetone detection (0.7 ppm) at 85% RH and is able to effectively differentiate diabetic patients from healthy subjects by detecting acetone in their exhaled breath. The enhanced response of Au-ZnO/ZnFe2O4-based sensor is attributed not only to its high specific surface area but also to the synergistic effect of the n–n heterojunction structure of ZnO-ZnFe2O4 and the catalysis of Au nanoparticles.